2016
DOI: 10.3390/coatings6010004
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antibacterial Composite Films Based on Isotactic Polypropylene and Coated ZnO Particles for Active Food Packaging

Abstract: This study was aimed at developing new films based on isotactic polypropylene (iPP) for food packaging applications using zinc oxide (ZnO) with submicron dimension particles obtained by spray pyrolysis. To improve compatibility with iPP, the ZnO particles were coated with stearic acid (ZnOc). Composites based on iPP with 2 wt % and 5 wt % of ZnOc were prepared in a twin-screw extruder and then filmed by a calender. The effect of ZnOc on the properties of iPP were assessed and compared with those obtained in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 38 publications
3
29
1
Order By: Relevance
“…It was incorporated in polycarbonate and the hydrophobic nanocomposites obtained showed antibacterial, UV-blocking properties [17]. Glass, low density polyethylene (LDPE), polypropylene (PP), polyurethane (PU), paper and chitosan, polyethylene [18] and polypropylene [19] were also coated with ZnO nanoparticles to obtain antimicrobial food packagings. Silver is well-known for its wide-range antimicrobial activity against both Gram-positive and Gram-negative bacteria (including antibiotic-resistant strains), fungi and certain viruses.…”
mentioning
confidence: 99%
“…It was incorporated in polycarbonate and the hydrophobic nanocomposites obtained showed antibacterial, UV-blocking properties [17]. Glass, low density polyethylene (LDPE), polypropylene (PP), polyurethane (PU), paper and chitosan, polyethylene [18] and polypropylene [19] were also coated with ZnO nanoparticles to obtain antimicrobial food packagings. Silver is well-known for its wide-range antimicrobial activity against both Gram-positive and Gram-negative bacteria (including antibiotic-resistant strains), fungi and certain viruses.…”
mentioning
confidence: 99%
“…This could be possibly due to very slow diffusion of the antimicrobials into the substrate where the bacteria grow. A recent study indicated that the main problem to be solved in adding ZnO nano/microparticles to a polymeric matrix seems therefore related to the formation of agglomerated domains that occur because of the strong intermolecular interactions among the ZnO particles in combination with their high surface area [11]. As a matter of fact, in our experiments using a model food system, LDPE activated with zinc oxide only induced a small delay on growth of L. innocua (as a surrogate of L. monocytogenes) in the vacuum-packaged seabream fillets.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7]. Application of these technologies in food packaging is, therefore, considered highly promising since these technologies could also improve safety and quality of food and the research is oriented not only to materials with increased mechanical properties and reduced permeability but also those having antimicrobial properties [8][9][10][11][12][13][14][15][16][17]. It has been shown that the use of active agents, incorporated in the polymeric material for packaging, increases the shelf-life of the packaged product (life duration of a foodstuff before its consumption), acting on those mechanisms of degradation that cause food deterioration and reducing/inhibiting the growth of pathogens [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This paper reports the results obtained using 5% of ZnO particles and of ZnO particles coated (ZnOc) with stearic acid in order to modify the characteristics of two polymers, one derived by oil, isotactic polypropylene (iPP), and the other derived from renewable resources, polylactide acid (PLA), largely used in the field of food packaging [8][9][10][35][36][37]. Considering our previous studies [8][9][10], it is believed that 5% is the best amount to use, in order to improve the characteristics of composites, especially for the antibacterial properties. To have a complete pattern of the two systems additional analysis have been performed and unpublished results will be presented.…”
Section: Introductionmentioning
confidence: 99%